A mild and efficient method for the synthesis of pyrroles using MIL-53(Al) as a catalyst under solvent-free sonication. Issue 16 (19th March 2019) - Nguyen, Hai Truong; Thuy Nguyen, Linh Ho; Le Hoang Doan, Tan; Tran, Phuong Hoang
Abstract : Catalytic activity of MIL-53(Al) in the synthesis of pyrroles under solvent-free sonication. Abstract : A highly efficient method for the synthesis of pyrroles using MIL-53(Al) as a catalyst has been developed under solvent-free sonication. This reaction has a broad substrate scope and high yields were obtained within a short reaction time. Remarkably, no additional additives and volatile organic solvent are required for this method and the MIL-53(Al) could be recovered and reused several times without significant drop-off in catalytic activity.